2010
DOI: 10.1007/s11999-009-1061-x
|View full text |Cite
|
Sign up to set email alerts
|

Revision Total Knee Arthroplasty for Aseptic and Septic Causes in Patients with Rheumatoid Arthritis

Abstract: Revision total knee arthroplasty in patients with rheumatoid arthritis can be challenging. We asked whether we could confirm previously reported high failure rates following revision total knee arthroplasty in patients with rheumatoid arthritis. We therefore determined the Knee Society knee score and function scores, radiographic evidence of failure, and overall survival of the revision procedure in these patients. We retrospectively reviewed 39 patients with rheumatoid arthritis who underwent 45 TKA revisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…There are limited data regarding the optimal treatment of PJI in patients with IJD. A recent retrospective review of revision TKA in patients with RA describes the outcomes of 18 cases of subacute and chronic PJI [12]. Of the 12 patients who received a two-stage revision, five of them subsequently died within 6 months, while three went on to have failures secondary to reinfection at a mean of 39.6 months.…”
Section: Resultsmentioning
confidence: 99%
“…There are limited data regarding the optimal treatment of PJI in patients with IJD. A recent retrospective review of revision TKA in patients with RA describes the outcomes of 18 cases of subacute and chronic PJI [12]. Of the 12 patients who received a two-stage revision, five of them subsequently died within 6 months, while three went on to have failures secondary to reinfection at a mean of 39.6 months.…”
Section: Resultsmentioning
confidence: 99%
“…Garcia et al report a survival for all knees (27 mechanical failures and 18 infected revisions) of 76% at 5 years. They also, more worryingly, report a 34 % mortality rate at 6 months for RA patients revised for infection [ 41 ].…”
Section: Revision Arthroplasty Surgerymentioning
confidence: 99%
“…It is shown that the implant survival rates in patients with inflammatory arthritis are less than those for uncomplicated degenerative osteoarthritis disease for several reasons. 19,20 Bourne et al 5 have shown that a sizable percentage (19%) of patients remain dissatisfied after TKA surgery. Tremendous advances have been made in the implant designs, refinement of the surgical treatment of TKR, and patient selection.…”
Section: Discussionmentioning
confidence: 99%